The erection of substation at UMK / Mohd Shafiq Dannial Abdullah - Abdullah, Mohd Shafiq Dannial (Universiti Teknologi Mara, Perak, 2016)
Blackfox Engineering was located at Lot 2040, Tingkat 1, Bangunan SBJ, 16250 Pasir Pekan, Wakaf Bharu, Kelantan. This company was incorporation on 03hb September 2003 by Azni Shah Bin Sulaiman, Director Management, and Mohd Rosman Zailani Mohd Ghazali, Director. Blackfox Engineering ran business for example construction, housing developer, and general trading. There are have two branch address at Kuala Lumpur and Johor Bharu. This company has a lot of experience in the field of construction involving major projects such as project proposal to modify and upgrade office space at headquarters building BSN, Kuala Lumpur. The contract period in 7 July 2012 until 7 January 2013. This contract worth as much RM12, 500,000.00. This owner for this project is a Bank Simpanan Nasional.